Does inclusive leadership foster employee psychological resilience? The role of perceived insider status and supportive organizational climate - Xintian, Li; Peng, Peng (Frontiers in Psychology, 2023)
Employee psychological resilience (EPR) correlates with individual performance and well-being which can effectively help employees cope with work pressure under a complex situation. Drawing upon the social identity theory and information processing theory, this paper explores how inclusive leadership (IL) stimulates employees' psychological resilience by integrating the cross-level mediating effects of perceived insider status (PIS). Notably, this study scrutinized the moderating function of supportive organizational climate (SOC) with inclusive leadership and the PIS of employees which expanded the inclusive leadership influence boundary. This study used a cross-sectional survey design and collected two-wave data from individuals who are currently employed in the context of Chinese organizations. Using multiple linear regression to analyze the paired survey data of 220 employees of valid samples, we conclude that: Inclusive leadership was positively related to employee psychological resilience; Perceived insider status mediated the relationship between inclusive leadership and employee psychological resilience; The indirect relationship above is moderated by supportive organizational climate such that the positive relationship will be enhanced when the supportive organizational climate is high, rather than low. Finally, the theoretical and practical implications of these findings are discussed.